Radio Carbon Dating and the Spread of Farming Economy - Clark, J. G. D.
auch Hacılar VII, Mersin, Ras Shamra, Tell Halaf, Tepe Sarab, Hajji Firuz, Jarmo, Matarrah, Zawi Chemi Shanidar, Hassuna, Tall-i-Bakun.